Effects of Aggression on Psychological Adjustment of College Students in District Faisalabad - Bushra Naoreen, Azhar Mumtaz Saadi, Jaffar Ali, (PJE, 2023)
Major objective of the current study was to find out the relationship between aggression and psychological adjustment among college students in district Faisalabad. Ten colleges (male=5 and female=5) were randomly selected from the population as sample. One thousand students (male=500 and female=500) were approached conveniently. Data were collected using two instruments: Adults Psychological Adjustment Survey (APAS) and Aggressive Behavior Scale (ABS). Descriptive statistics and pearson r were used to analyze the data. Findings indicated above average level of aggression and below average level of psychological adjustment among college students and a significantly positive relationship between aggression and psychological adjustment. As the level of aggression increases, it weakens the psychological adjustment. All the sub factors of aggression are significantly correlated with sub factors of psychological adjustment. It is recommended that during admission process, students’ aggression and psychological adjustment must be considered in addition to academic qualification.